The Integration of Transportation Route of Industrial Area and Lurik Tourism for Production and Sales Optimization - Galing Yudana; Istijabatul Aliyah; Rara Sugiarti (Department of Urban and Regional Planning, Diponegoro University, 2019)
The development of industrial and tourism areas brings the consequences of the arrangement of transportation routes. As an industrial area as well as lurik tourism, Klaten District becomes the research location with the aim to know the mapping of access and integration of industrial transportation and lurik tourism route in order to optimize production and sales. The method employed in this research was digital mapping through GIS, and super impos analysis of mapping results to get integrated integration. The results reveal that transportation routes naturally form a pattern of industrial circulation with the orientation of efficiency and independence of distribution and sales of lurik products. Meanwhile the pattern of tourism circulation is formed with the orientation of interconnection between industry and tourism support facilities. The established integration can be optimized through the implementation of thematic tourism concepts by integrating smoothness, security, and easy access point between industries and lurik tourism.